Genetic diversity analysis in coriander (Coriandrum sativum) varieties - MEENA, R S; KAKANI, R K; CHOUDHARY, SHARDA; SINGH, BALRAJ; PANWAR, ALKA (The Indian Journal of Agricultural Sciences, 2014)
Twenty four varieties of coriander (Coriandrum sativum L.), developed by different centres which located at diverse eco-geographical origins of the country, were undertaken in present investigations to determine divergence for seed yield and its 10 component traits. Tocher method of hierarchical cluster analysis was applied to group the varieties. Varieties were grouped into four clusters. All varieties were grouped in four clusters that showed narrow genetics base of Indian varieties. Intra-cluster distance was highest in cluster III followed by cluster II, IV and I. The maximum inter-cluster distance was between clusters III and I are 17.91 and 3.86 respectively. The varieties in cluster I were Hisar Sugandh, Hisar Anand, RCr-20, RCr-435, RCr-436, RCr-446, RCr-684, Swathi, Sadhana, Sindhu, Sudha, Rajendra Swati, GCr-1, GCr-2, CO-1, CO-2, CO-3, CO-4. The variety falling in cluster II is JD-1.The varieties falling in cluster III were NRCSS ACr-1, RCr-41and Azad Dhania-1. The varieties falling in cluster IV were Hisar Surubhi and Pant Haritma. Among the 10 characters studied for genetic divergence, days to 50% flowering contributed the maximum accounting for 49.64% of total divergence, followed by test weight (17.03%).